Comparison of the effects of pemafibrate and omega-3 fatty acid ethyl on fatty liver index in patients with dyslipidemia treated with statin: a sub-analysis from the PROUD48 study - Takeda, Yasutaka; Furuhashi, Masato; Sakuma, Ichiro; Hiramitsu, Shinya; Okada, Mizuho; Ueda, Shinichiro; Kumashiro, Naoki; Sakurai, Masaru (Frontiers in Endocrinology, 2025)
BackgroundFatty liver index (FLI) calculated by using body mass index, waist circumference and levels of triglycerides and γ-glutamyl transpeptidase is a noninvasive biomarker for diagnosis of metabolic dysfunction-associated steatotic liver disease (MASLD), which is one of the high-risk conditions of atherosclerotic cardiovascular diseases. To compare the effects of pemafibrate and omega-3 fatty acid ethyl on FLI, we conducted a sub-analysis study of the Pemafibrate Reduction of triglyceride-rich lipoproteins compared with Omega-3 fatty acid ethyl for Unmet needs in Dyslipidemic patients on target to apoB-48 (PROUD48) study.Methods57 participants in the pemafibrate 0.4 mg per day treatment group (PEMA, men/women: 37/20, mean 64 years) and 60 participants in the omega-3 fatty acid ethyl 4 g per day treatment group (OMEGA-3, men/women: 35/25, mean 63 years) in the PROUD48 study were included in the present study. Changes in FLI and prevalence of MASLD from baseline to week 16 in PEMA and OMEGA-3 were investigated.ResultsMedian FLI was significantly decreased by both PEMA (69.7 to 47.6, P < 0.001) and OMEGA-3 (64.8 to 59.5, P < 0.001). There was a significant difference in change in FLI between PEMA and OMEGA-3 (-18.3 ± 14.1 vs. -5.5 ± 9.4, P < 0.001). The proportions of MASLD estimated by FLI (baseline/week 16) in PEMA and OMEGA-3 were 93.0/68.4% (P = 0.002) and 90.0/85.0% (P = 0.582), respectively.ConclusionsPemafibrate is superior to omega-3 fatty acid ethyl in lowering effects of FLI and MASLD in patients with dyslipidemia receiving statin treatment, suggesting that pemafibrate is a beneficial agent for hypertriglyceridemia and reduction of the risk for MASLD.